Reinterpretacja i renarracja ballady Adama Mickiewicza w filmie Świtezianka Julii i Mai Bui Ngoc = Reinterpretation and Renarrative of Adam Mickiewicz`s Ballad in The Film Świtezianka by Julia and Mai Bui Ngoc - Rawski, Jakub (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the article is to analyze the phenomenon of reinterpretation and renarrative of Adam Mickiewicz`s Świtezianka (1822) in Julia and Mai Bui Ngoc`s film of the same title (2018). Polish directors of Vietnamese origin undertook a cognitively interesting task - translating, or rather adapting, the romantic ballad plot to contemporary realities and merging literary and film language.
Keywords: reinterpretacja; renarracja; ballada; Mickiewicz, Adam (1798-1855). Świtezianka; romantyzm; film; reinterpretation; renarrative; ballad; romanticism